Introduction to social media investigation : a hands-on approach - Golbeck, Jennifer (Walthan, MA : Syngress, 2015)
Social networks and social media, like Facebook, Twitter, LinkedIn and Foursquare, are some of the most popular services on the Web, with hundreds of millions of users. The public information that people share on these sites can be valuable for anyone interested in investigating people of interest through open, public sources. This book presents an overview of social media and discusses special skills and techniques to use when conducting investigations. It features hands-on tutorials and case studies and offers additional data-gathering techniques. --
Print version record.
Includes bibliographical references and index.
Keywords: Online social networks; Data mining; Criminal investigation; Criminal investigation; Data mining; Online social networks; Electronic books; Electronic book